(untitled) (Revista Científica Integrada, 2025)
Objective: To critically report an experience of a Supervised Psychology Internship in Primary Health Care (PHC), carried out by students from the Federal University of Amazonas (UFAM) at a Basic Health Unit (BHU) located in the eastern zone of Manaus. Method: The experience report is adopted as the methodological approach, understood as a production of meanings arising from affective displacements, challenges, and everyday practices during the internship. Thematic analysis was articulated based on the Technical Guidelines for the Work of Psychologists in Primary Health Care of the Brazilian Unified Health System (SUS). Results: The main practices included waiting-room activities, individual consultations, interventions in the School Health Program (PSE), and home visits. These experiences reveal an expanded and contextualized form of clinical practice—sensitive to bonds, social contexts, and vulnerabilities. At the same time, they highlight both structural and symbolic limitations of Psychology within PHC, such as competition for space, institutional precariousness, and the persistence of traditional clinical models. Conclusion: It is concluded that Psychology training in PHC requires professional engagement with the local territory and the collective construction of care, promoting an ethical, political, and creative practice.